(untitled) (The International Journal of Educational Sciences and Arts, 2026)
This study aimed to identify the extent to which principals of private schools in the capital (Amman) possess the competencies required for integrating students with disabilities into supportive education programs, from the teachers’ perspectives. The study population consisted of (2,500) teachers working in private schools in Amman, and an accessible sample of (335) teachers was selected. The researchers employed the correlational descriptive method, and data were collected using a questionnaire after verifying its validity and reliability. The results revealed that principals’ overall level of competencies was moderate, with affective competencies ranking highest, followed by social competencies, while organizational competencies ranked lowest. The findings also showed that female principals outperformed males in organizational, social, and affective competencies, while no statistically significant differences were found based on academic qualification. Moreover, the results indicated that principals with more than ten years of experience scored higher in affective competencies only. The results emphasized the need to strengthen organizational, educational, and professional competencies, develop principal preparation programs to include practical applications in inclusion, enhance affective and social competencies for new principals and those with fewer than ten years of experience, create inclusive classroom environments, monitor student performance, and utilize supportive teaching tools and technologies to ensure the quality of inclusive education and support programs. The researchers recommended enhancing principals’ competencies in the organizational, educational, professional, administrative, affective, and social domains through specialized training programs and improving leadership preparation programs. It also called for expanding research to build a national competency framework. Additionally, the study stressed the importance of forming individualized follow-up teams for students with disabilities, providing inclusive classroom environments, organizing professional meetings for teachers, activating psychological counseling, designing collaborative activities, ensuring continuous assessment, and promoting the use of supportive educational technologies to improve the integration process.